Non-pharmacological prevention of pregnancy complications in women with hypertension in the context of military operations in Ukraine - A. Ye. Husieva; M. Ye. Kyrylchuk (Zaporožskij Medicinskij Žurnal, 2025)
Aim. To assess anxiety levels in pregnant women with hypertensive disorders (HDs) and the effectiveness of the developed complex non-drug relaxation measures in conditions of military operations in Ukraine.